Thermodiffusion in multicomponent n-alkane mixtures - Guillaume Galliero (Nature Portfolio, 2017)
Microgravity simulators: improving oil field assessments To support oil and gas exploration, researchers sent hydrocarbon mixtures into space to obtain accurate data on how each component behaves. The group—led by Guillaume Galliero from the University of Pau and Pays de l’Adour, France—wanted to study the effect of temperature on the movement of individual hydrocarbons in mixtures under typical reservoir conditions. Eliminating the effects of gravity allowed them to collect more accurate data than has previously been obtained. The team showed that thermodiffusion has a large impact on the distribution of hydrocarbon reservoirs under the ground. They state that thermodiffusion should therefore be considered in computer models that assess analytical data collected at potential underground reservoirs. This would allow oil and gas companies to more accurately predict the suitability of the hydrocarbons at potential drilling sites.